The investigation of perception and satisfaction on e-hailing service among undergraduate students of Universiti Tunku Abdul Rahman - Tan, Jei Ru; Tan, Yu Xuan; Tong, Chia Chian (2023)
In recent years, e-hailing firms have provided a new option to public transportation by providing private automobile services. E-hailing apps make public transit more accessible. However, users sometimes complain about e-hailing services, such as overpricing, driver misbehaviour, or safety issues. Grab is Malaysia's top ride-hailing service. This research examines Universiti Tunku Abdul Rahman undergraduate students' perception and satisfaction with e-hailing services. Besides, this research uses a quantitative survey questionnaire to collect data. The final analysis employs the Statistical Package for the Social Sciences (SPSS). The study includes descriptive, reliability, and inferential analyses. This study evaluate the dependent variable, user satisfaction level among UTAR students on the e-hailing service, by analyzing the independent variables, including perceived pricing, driver behaviour, IV perceived safety and security, and perceived reliability. The results of the study indicate that the majority of respondents expressed a high level of satisfaction with e-hailing services. This study also uses the Pearson Correlation Coefficient Model (PCC) and Multiple Linear Regression Model (MLR) models to determine the factors influencing UTAR undergraduate students' satisfaction with e-hailing services.